2020
DOI: 10.1111/jan.14401
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional multisite exploration of Italian paediatric nurses’ reported burnout and its relationship to perceptions of clinical safety and adverse events using the RN4CAST@IT‐Ped

Abstract: To explore Italian paediatric nurses' reported burnout and it relationship to their perceptions of safety and adverse events. DesignA cross-sectional study utilizing the RN4CAST@IT-Ped database using a web based survey design. MethodsThe RN4CAST@IT-Ped questionnaire was used to collect data in 2017. This comprised three main components: three dimensions (22 items) of the Maslach Burnout Inventory including emotional exhaustion, depersonalization and personal accomplishment.Participants also scored an overall g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…While studies investigating the occurrences of AEs among the health care staff during the COVID-19 pandemic are limited, a review of the studies conducted before the COVID-19 pandemic revealed that 29.1% of the surveyed nurses had experienced AEs in the last 6 months (Kakemam, Kalhor, et al, 2019). Findings of a study conducted in China show the occurrence of AEs ranging from 47.8% to 75.6% (Wang et al, 2014), which is higher than the findings of a study conducted among Italian paediatric nurses that showed the occurrence of AEs ranging from 1.3% to 12.4% (Bagnasco et al, 2020). One study found that the rate of AEs reporting has reduced following the onset of the COVID-19 pandemic (Denning, Goh, Scott, et al, 2020).…”
Section: Ta B L Ementioning
confidence: 81%
See 3 more Smart Citations
“…While studies investigating the occurrences of AEs among the health care staff during the COVID-19 pandemic are limited, a review of the studies conducted before the COVID-19 pandemic revealed that 29.1% of the surveyed nurses had experienced AEs in the last 6 months (Kakemam, Kalhor, et al, 2019). Findings of a study conducted in China show the occurrence of AEs ranging from 47.8% to 75.6% (Wang et al, 2014), which is higher than the findings of a study conducted among Italian paediatric nurses that showed the occurrence of AEs ranging from 1.3% to 12.4% (Bagnasco et al, 2020). One study found that the rate of AEs reporting has reduced following the onset of the COVID-19 pandemic (Denning, Goh, Scott, et al, 2020).…”
Section: Ta B L Ementioning
confidence: 81%
“…The findings of the study are congruent with similar ones in the literature in which high levels of burnout are reported to correlate with increased medication errors and increased patient falls (Nantsupawat et al, 2016;Van Bogaert et al, 2014), increased patient and family verbal abuse, as well as patient and family complaints (Van Bogaert et al, 2014), and increased infections (Cimiotti et al, 2012;Nantsupawat et al, 2016;Van Bogaert et al, 2014) and revealed a similar association between nurse burnout and AEs in the Iranian setting. A study in the Italian paediatric context has consistently shown that nurse burnout is associated with higher AEs (Bagnasco et al, 2020). Burnout was found to raise medical errors among health care staff, particularly in physicians (Fahrenkopf et al, 2008;Shanafelt et al, 2010).…”
Section: Ta B L Ementioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have reported negative consequences of burnout on nurses' health such as insomnia, irritability, headaches, or related it with anxiety and depression [9,10]. In addition, there are also studies that report that burnout increases the number of mistakes at work, reduced the quality and safety of care, and that it favors sick leave or abandonment of the profession [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%